Ouran High School Host Club. Vol. 12 - Hatori, Bisco (Shojo beat manga., 2009)
"Hikaru and Kaoru's fight over Haruhi is taking its toll on Hunny and Mori, who are trying to watch over the estranged twins. Meanwhile, unbeknownst to Tamaki, Kyoya starts looking for Tamaki's mother in France."--P. [4] of cover.